(untitled) (Journal of Universal Science Research, 2023)
Middle English language, the vernacular spoken and written in England from about 1100 to about 1500, the descendant of the Old English language and the ancestor of Modern English.The history of Middle English is often divided into three periods: (1) Early Middle English, from about 1100 to about 1250, during which the Old English system of writing was still in use; (2) the Central Middle English period from about 1250 to about 1400, which was marked by the gradual formation of literary dialects, the use of an orthography greatly influenced by the Anglo-Norman writing system, the loss of pronunciation of final unaccented -e, and the borrowing of large numbers of Anglo-Norman words; the period was especially marked by the rise of the London dialect, in the hands of such writers as John Gower and Geoffrey Chaucer; and (3) Late Middle English, from about 1400 to about 1500, which was marked by the spread of the London literary dialect and the gradual cleavage between the Scottish dialect and the other northern dialects.